Atypical Variants of Right Ventricular Outflow Arrhythmias. (12th August 2014) - MULPURU, SIVA K.; KONECNY, TOMAS; MADHAVAN, MALINI; KAPA, SURAJ; NOSEWORTHY, PETER A.; MCLEOD, CHRISTOPHER J.; FRIEDMAN, PAUL A.; PACKER, DOUGLAS L.; ASIRVATHAM, SAMUEL J.
RVOT Atypical Variants Background Right ventricular outflow tract (RVOT) arrhythmias are a common form of ventricular tachycardia (VT) in patients with structurally normal heart. The underlying mechanism is due to triggered activity. Mapping and ablation is relatively straightforward targeting the earliest point of activation. Previously reported causes of difficult ablation in the RVOT region include under recognized right ventricular cardiomyopathy/sarcoidosis, presence of endocavitary structures, close proximity to the coronary vasculature, and origin from non‐RVOT structures. Methods and Results We identified all patients undergoing PVCs/sustained RVOT VT ablation from January 2013 to December 2013. This included 33 patients. Of these, we identified procedures that were considered difficult despite a single morphology arrhythmia being targeted and no underlying cardiomyopathy present. Difficulty was specifically considered when ablation at the earliest site of activation was not successful and eventual successful ablation was at a distance of greater than 15 mm from the early activation site. We identified 3 patients (n = 3, 100% male) with evidence of reentrant arrhythmia based on slow conduction zones necessary for the tachycardia/arrhythmia, mid diastolic signals during VT or preceding bigeminal PVCs, pace mapping from the site abnormal signals reproducing the arrhythmia morphology but with prominent conduction delay, the entire cycle length of the tachycardia or coupling interval for the PVCs being mapping, or based on reset characteristics. Conclusion In patients with atypical forms of RVOT VT, careful mapping and ablation of the myocardial sleeves near the pulmonic valve can eliminate the arrhythmia.